Dinamika Psikologis Perempuan Bali Dengan Status Istri yang Tidak Memiliki Anak Laki-Laki Pada Pernikahan Hindu Etnis Bali - Paramita, I Gusti Agung Ayu Istri Sripradnya; Dewi, Ni Nyoman Ari Indra; Hardika, I Rai (Jurnal Ilmiah Wahana Pendidikan, 2025)
The patrilineal system that the Indonesian people are interpreted that the structure of the kinship is based on the offline. Men's position also holds the right in the heirs. For the Bali Hindu family who has no boys raises concerns if there is no successor in the family to continue the duties and obligations of parents in the family and customs. So bring up a psychological conflict in a wife who does not have a boy in his marriage. This study aims to describe and explore the psychological dynamics experienced by a wife who has no boys at Balinese wine ethnic wedding. The method used in this research is qualitative method with case study approach. Data collection techniques using interviews, observation, and documentation performed against Balinese women with the status of the wife. This research focuses on aspects of psychological dynamics including cognitive, affective, and associated associated. The results of the study show that the occurrence of psychological changes in the wife who has no boy is from internal and external pressure or environment with cultural attribution and customs that are enacted by the people of Bali related to patrilineal kinship. The presence of self-awareness a.nd acceptance, as well as the contribution of social support received by a wife who has no boy drafting on a positive psychological dynamics in cognitive, affective, and calibatan cases can work properly.